Jaka wizja edukacji wyłania się z transhumanistycznego chaosu? - Klichowski, Michał; Janczarczyk, Małgorzata; Walkowiak, Hanna; Kowalska, Klaudia; Głowacka, Paulina (My University, 2015)
Transhumanism is a philosophy whose essence is to use technology to overcome biological limitations of the man and improve the human condition. This overcoming and improvement are understood as freeing the man from illnesses, ageing processes, and achieving the state of full happiness, permanent, top excitement, as well as replacing many organs (and the entire body at some point) with artificial elements (better than the original ones). Transhumanism calls for maximum development and popularization of technology so that the above-mentioned full overcoming and human improvement could occur as soon as possible. This paper presents basic transhumanism ideas, stress the vision of education created within this philosophy and shows transhumanist projects (Clouds over Sidra, Eyeborg, VEST and BrainGate) that can transform education.

Transhumanizm to filozofia, której istotą jest wykorzystanie techniki do przezwyciężenia biologicznych ograniczeń człowieka i poprawy ludzkiej kondycji. Owe przezwyciężenie i poprawa rozumiane są jako uwolnienie człowieka od chorób, procesów starzenia, oraz uzyskanie przez niego pełni szczęścia i – permanentnej – szczytowej ekscytacji, a także zastąpienie wielu z jego organów (a kiedyś i całego ciała) sztucznymi (lepszymi od pierwowzorów) elementami. Transhumanizm postuluje maksymalne rozwijanie i upowszechnianie techniki, tak by wspomniane całkowite przezwyciężenie i ulepszenie człowieka mogło nastąpić jak najszybciej. Artykuł ten przedstawia podstawowe idee transhumanizmu, akcentuje wizję edukacji skonstruowaną w obrębie tej filozofii oraz ukazuje transhumanistyczne projekty (Clouds over Sidra, Eyeborg, VEST i BrainGate) mogące odmienić edukację.
What vision of education emerges from the transhumanist chaos?
Keywords: transhumanizm; przyszłość edukacji; projekt BrainGate; projekt VEST; projekt Eyeborg; projekt Clouds over Sidra; transhumanism; future of education; project Clouds over Sidra; project Eyeborg; project VEST; project BrainGate